An estimation model for anaerobic power of taekwondo athletes based on field tests - Kwon, C.; Lee, S.; Park, J.; Johnson, J. A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2019)
Background. Anaerobic power is measured in Taekwondo with short-term explosive kicking and the muscle strength and endurance needed to push an opponent, has become extremely high. In previous studies, anaerobic power tests were developed but are inconvenient and somewhat lacking for Taekwondo athletes. Problem and Aim. In order to design an estimation model to measure variables in Taekwondo roundhouse kick field tests, the Wingate anaerobic power test was applied to the kicking speeds of 20 male elite-level Taekwondo players` in laboratory and field tests over a three-week period. Methods. To estimate anaerobic power capability, laboratory tests included 30- and 90-second Wingate tests, and field tests included standard fitness tests and performing one set of Taekwondo roundhouse kicks at peak speed on three consecutive days for 30, 60, and 90 seconds, respectively. Variables were subjected to mean comparison, correlation, and multiple regression analysis by subjects` weight class. The Wingate test was used to estimate anaerobic power capability. Results. Anaerobic power measured by the Wingate test significantly affected Taekwondo kicking performance for 0-5 seconds and 10-15 seconds, 50m running, and standing long jump tests. Conclusions. The results of this study suggest that utilizing 30 seconds of continuous kicking at peak speed, 50m running, and standing long jump are possible field tests components for an estimation model to determine anaerobic power capability in Taekwondo athletes.